Efektivitas Pembelajaran Kimia Berbasis Proyek Inovatif dalam Meningkatkan Kemampuan Berpikir Kritis Siswa Sekolah Menengah Atas - Afrahamiryano, Afrahamiryano; Yora, Muharama (Pendidikan Biologi FKIP UMMY, 2025)
Critical thinking skills require a fundamental understanding of content in order to understand, analyze, and evaluate information. Therefore, learning critical thinking skills requires a good combination of student-centered learning and teacher-centered learning. One such student-centered learning approach is Project-Based Learning (PjBL). The purpose of this study was to determine the differences in critical thinking skills of students who learn chemistry using innovative project-based learning and those without innovative project-based learning. The sample in this study was students of class XII MIPA 3 (Control Class) and class XII MIPA 4 (Experimental Class) of SMA Negeri 3 Solok. Based on the test results, it was found that there were differences in critical thinking skills between students who learned chemistry using innovative project-based learning and those without innovative project-based learning. Where the results of the Independent Samples Test - T showed that the p-value was > 0.05. So it can be concluded that the critical thinking skills of students who learned chemistry using innovative project-based learning were better than those without innovative project-based learning.